Cultura y ambiente en la Sierra de Misantla, Veracruz, México: el caso de Oecopetalum mexicanum - Lascurain Rangel, Maite; López Binnqüist, Citlalli; Emery, Marla (Instituto de Ecología, A.C., 2016)
Culture and environment in the Sierra de Misantla, Veracruz, Mexico: the case of Oecopetalum mexicanumWe analyze the cultural and environmental dimensions of foraging the wild edible fruit cachichín (Oecopetalum mexicanum) in the Sierra de Misantla in central Veracruz, Mexico, including gathering practices, social organization, subsistence, commerce, and consumption. Gathering cachichínbrings together generations and genders in practices that provide amusement, as well as resources for economic income and personal consumption. Socialization during the gathering of cachichín renews and strengthens family bonds, friendships, and a sense of belonging. This study provides valuable insights for management, use and conservation of non-timber forest resources with biocultural roots.